PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATERI BANGUN RUANG SISI DATAR KUBUS DAN BALOK KELAS VIII SMP - Nadia Hairul Nissa; Aulia Sthephani; Leo Adhar Effendi; Lilis Marlina Anggraini (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2022)
ABSTRACT The development of android-based learning media is undercover in research and development. This study aims to see the results of the validity of the expansion of android-based learning media on the material for building flat sides of cubes and blocks for class VIII Junior High School. In this study, the development model refers to the R&D development model that has been according to the needs of the researcher, with the stages: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) the final product. The research instrument used is validation. The data collection technique used a validation sheet with a Likert scale. The data analysis technique used is descriptive analysis. In the potential and problem stage, the researcher analyzes the educational situation and interviews, then collected data related to the potential and problems. After that the researchers designed the design of learning media products. The results of the analysis of research validation by three validators obtained an average validation of learning media of 82.87% that is category is quite valid or can be late with minor revisions. The conclusion of the study showed that the android-based learning media was tested valid. Keywords: Learning Media, Android, R&D, Build Flat Side Space